Oral health-related KAP among 11- to 12-year-old school children in a government-aided missionary school of Bangalore city - Harikiran A; Pallavi S; Hariprakash Sapna; Ashutosh; Nagesh K (Wolters Kluwer Medknow Publications, 2008)
Background: To organize community-oriented oral health promotion programs systematic analysis of the oral health situation would be needed, including information on oral health knowledge, attitudes, and practices (KAP). Aim: The aim of this study was to assess knowledge, attitude, and practice (KAP) toward oral health among 11 to 12-year-old school children in a government-aided missionary school of Bangalore city. Materials and Methods: The study group comprised of 212 children (Male: 108; Female; 104) who were in the age group of 11-12 years studying in a government-aided missionary school of Bangalore city. Data on oral health KAP were collected by means of a self-administered questionnaire. Statistical significance was determined by Chi-square test. Results: This survey found that only 38.5% of the children brush their teeth two or more times a day. Pain and discomfort from teeth (35.1%) were common while dental visits were infrequent. Fear of the dentist was the main cause of irregular visit in 46.1% of study participants. High proportion of study participants reported having hidden sugar at least once a day: soft drinks (32.1%), milk with sugar (65.9%), and tea with sugar (56.1%). It was found that 5.4% and 3.9% of study participants smoke and chew tobacco, respectively. Conclusion: Results of this study suggest that oral health KAP of study participants are poor and needs to be improved. Systematic community-oriented oral health promotion programs are needed to improve oral health KAP of school children.